Biosynthesis of polyhydroxybutyrate by Methylorubrum extorquens DSM13060 is essential for intracellular colonization in plant endosymbiosis - Baruah, Namrata; Haajanen, Roosa; Rahman, Mohammad Tanvir; Pirttilä, Anna Maria; Koskimäki, Janne J. (Frontiers in Plant Science, 2024)
Methylorubrum extorquens DSM13060 is an endosymbiont that lives in the cells of shoot tip meristems. The bacterium is methylotrophic and consumes plant-derived methanol for the production of polyhydroxybutyrate (PHB). The PHB provides protection against oxidative stress for both host and endosymbiont cells through its fragments, methyl-esterified 3-hydroxybutyrate (ME-3HB) oligomers. We evaluated the role of the genes involved in the production of ME-3HB oligomers in the host colonization by the endosymbiont M. extorquens DSM13060 through targeted genetic mutations. The strains with deletions in PHB synthase (phaC), PHB depolymerase (phaZ1), and a transcription factor (phaR) showed altered PHB granule characteristics, as ΔphaC had a significantly low number of granules, ΔphaR had a significantly increased number of granules, and ΔphaZ1 had significantly large PHB granules in the bacterial cells. When the deletion strains were exposed to oxidative stress, the ΔphaC strain was sensitive to 10 mM HO× and 20 mM H2O2. The colonization of the host, Scots pine (Pinus sylvestris L.), by the deletion strains varied greatly. The deletion strain ΔphaR colonized the host mainly intercellularly, whereas the ΔphaZ1 strain was a slightly poorer colonizer than the control. The deletion strain ΔphaC lacked the colonization potential, living mainly on the surfaces of the epidermis of pine roots and shoots in contrast to the control, which intracellularly colonized all pine tissues within the study period. In earlier studies, deletions within the PHB metabolic pathway have had a minor effect on plant colonization by rhizobia. We have previously shown the association between ME-3HB oligomers, produced by PhaC and PhaZ1, and the ability to alleviate host-generated oxidative stress during plant infection by the endosymbiont M. extorquens DSM13060. Our current results show that the low capacity for PHB synthesis leads to poor tolerance of oxidative stress and loss of colonization potential by the endosymbiont. Altogether, our findings demonstrate that the metabolism of PHB in M. extorquens DSM13060 is an important trait in the non-rhizobial endosymbiosis.